Pembentukan Pemahaman Karakter Kejujuran Melalui Permainan Tradisional di RA. Amanah Kecamatan Medan Marelan - Hadriany, Elvi; Kurniati, Qori; Thifa, Lumaru; Ramadhani, Putri (AUD Cendekia: Journal of Islamic Early Childhood Education, 2021)
This study aims to influence children on the importance of character education that can be seen from traditional games. The method carried out by questionnaires and interviews with teachers in ra Yayasan Amanah school, in addition to introducing Indonesian cultural assets early on to children of some games also provides many functions in the world of education. Coklak and engklek games for example in addition to the value of honesty contained in the game there is also the value of cooperation, compactness, independence, and there is more.